Anthelmintic Resistance in Livestock Farming: Challenges and Perceptions of Farmers and Veterinarians - Naida Kapo; Adis Softić; Teufik Goletić; Šejla Goletić; Aleksandar Cvetkovikj; Jasmin Omeragić (Pathogens, 2025)
Anthelmintic resistance in livestock is a growing concern worldwide, with significant implications for animal health and agricultural productivity. This study explores the perceptions of veterinarians and farmers in Bosnia and Herzegovina regarding the factors contributing to anthelmintic resistance in Haemonchus contortus nematodes. Data were collected through structured questionnaires completed by 106 veterinarians and 188 farmers in 2022 and 2023. The analysis focused on self-reported therapeutic practices, farm management and environmental variables. Logistic regression, including Firth’s penalized approach, was used to assess associations between these perceived factors and the reported occurrence of resistance. Notably, combination anthelmintic treatments were perceived as a significant risk factor (OR > 49.3), while higher altitude was seen as potentially protective (OR = 0.10). Routine prophylactic deworming was associated with an increased likelihood of perceived resistance (OR = 173.7), whereas staying informed about newly registered products was perceived as protective (OR = 0.34). Although the findings are based on the self-reported perceptions and practices of veterinarians and farmers, they align with globally recognized trends and offer the first structured insights into factors perceived to contribute to anthelmintic resistance in Bosnia and Herzegovina. This study underscores the importance of awareness and responsible anthelmintic use and the need for improved diagnostics and ongoing education to combat anthelmintic resistance.